2020
DOI: 10.1111/dth.14265
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus and COVID ‐19: Critical overview of management with a focus on treatment choice

Abstract: COVID-19 is a serious multisystem disease caused by severe acute respiratory syndrome coronavirus 2. Due to the COVID-19 crisis, that still keeps its impacts worldwide, numerous scheduled medical activities have been postponed and this interruption has a potential to modify the management of many cutaneous conditions including pemphigus. This narrative review aims to discuss the management of pemphigus in the era of COVID-19, considering the necessity to balance suitable pemphigus treatment with minimal risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Table 3 shows other COVID-related autoimmune disease treated with IVIg. [109][110][111][112][113][114][115] Finally, it is important to pay attention to the post-COVID (ie short-term) and long-COVID (ie long-term) manifestations appearing in people recovering from the SARS-CoV-2 infection. Any organ system can be involved, in particular immune system.…”
Section: Induced Autoimmune Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows other COVID-related autoimmune disease treated with IVIg. [109][110][111][112][113][114][115] Finally, it is important to pay attention to the post-COVID (ie short-term) and long-COVID (ie long-term) manifestations appearing in people recovering from the SARS-CoV-2 infection. Any organ system can be involved, in particular immune system.…”
Section: Induced Autoimmune Diseasesmentioning
confidence: 99%
“…Table 3 shows other COVID‐related autoimmune disease treated with IVIg. 109 , 110 , 111 , 112 , 113 , 114 , 115 …”
Section: Ivig In Sars‐cov‐2 Induced Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as it can lead to higher susceptibility to infections, concerns about its use during the pandemic have been raised (2). Some authors have suggested avoiding or temporarily postponing RTX during the pandemic due to the risk of SARS-CoV-2 infection (2,12).…”
Section: Introductionmentioning
confidence: 99%
“… 1 However, because of the immunosuppressive background of the autoimmune disorder itself and the immunosuppressive drugs used in the treatment of these diseases, it is reasonable to think that these patients have a higher susceptibility to bacterial and viral infections. 2 , 3 For this reason, EADV guidelines recommend checking for an up‐to‐date vaccination status before starting an immunosuppressive treatment and regularly performing standard vaccinations (influenza, pneumococci, tetanus, pertussis, etc). The only contraindication is the use of live vaccines in patients treated with adjuvant immunosuppressants and rituximab.…”
mentioning
confidence: 99%